2018
DOI: 10.1021/acsabm.8b00282
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Collagen-Rich Extracellular Matrix Hydrogels and Their Functionalization with Poly(ethylene glycol) Derivatives for Enhanced Biomedical Applications: A Review

Abstract: The hydrogels of natural extracellular matrix (ECM) are excellent biomaterials with promising applications in the physiological manufacture of three-dimensional (3D) constructs that replicate native tissue-like architectures and function as cargo-delivery, 3D bioprinting, or injectable systems. ECM hydrogels retain the bioactivity to trigger key cellular processes in the tissue engineering and regenerative medicine (TERM) strategies. However, they lack suitable physicochemical properties, which restricts their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 134 publications
0
17
0
Order By: Relevance
“…It has been reported that the polymerization of collagen to form fibers depends on the concentration of PU, and that concentrations in weight higher than 60% prevent the process of collagen fibrilogenesis 21 . Other systems of semi‐IPN collagen hydrogels with PVA, 8 PEG, 9 chitosan 15,16 and cellulose 19 reveal that concentrations less than 10 wt% of the components do not alter the capacity of collagen fiber formation, generating fibrillary semi‐interpenetrated systems with these chemical agents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that the polymerization of collagen to form fibers depends on the concentration of PU, and that concentrations in weight higher than 60% prevent the process of collagen fibrilogenesis 21 . Other systems of semi‐IPN collagen hydrogels with PVA, 8 PEG, 9 chitosan 15,16 and cellulose 19 reveal that concentrations less than 10 wt% of the components do not alter the capacity of collagen fiber formation, generating fibrillary semi‐interpenetrated systems with these chemical agents.…”
Section: Resultsmentioning
confidence: 99%
“…For it, several chemical cross-linkers that have been used: genipin, glutaraldehyde, carbodiimide, PEG derivatized with reactive groups, among others. 3,9,11,12 Recently, a novel method for the preparation of crosslinked collagen hydrogels with trifunctional polyurethane prepolymers (PPU) has been reported. 13 The urea cross-linking bonds produced by the condensation reaction of the primary amino groups of the collagen with the isocyanate ends of PPU produce hybrid 3D matrices with tailored mechanical properties, improved swelling capacity and regulated proteolytic degradation rate, despite that, this system does not present antibacterial capacity and limits cell viability to high concentrations of PPU by cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the poor mechanical properties of natural protein hydrogels is one of the main drawbacks impeding their application in some cases (Silva et al, 2017;Tang et al, 2018). Recently, great efforts have been made to enhance the mechanical properties of natural protein hydrogels, and some strategies have been developed, including nanocomposite (Yuk et al, 2016;Qin et al, 2017;Wang et al, 2017Wang et al, , 2018, physical cross-linking (Toivonen et al, 2015;Feng et al, 2018;Yan et al, 2019;Zhang et al, 2019), solvent induction (Li et al, 2016;Zhang et al, 2016;Hashemnejad et al, 2017;Zhu et al, 2018), double network (Bhattacharjee et al, 2015;Luo et al, 2016;Rangel-Argote et al, 2018;Tavsanli and Okay, 2019), hybrid cross-linking (Moura et al, 2011;Epstein-Barash et al, 2012;Xu et al, 2016;Nojima and Iyoda, 2018;Yang et al, 2018), and so on.…”
Section: Introductionmentioning
confidence: 99%